A proposal for reforming the Stability and Growth Pact - Philippa Sigl-Glöckner; Max Krahé; Florian Kern; Florian Schuster (Dezernat Zukunft e.V., 2022)
There is consensus that the Stability and Growth Pact (SGP) needs to evolve. In this paper, we put forward reform ideas aimed at reducing debt levels, enabling sustainable growth and strengthening Europe's sovereignty without a change in primary legislation. The current fiscal framework leads to a suboptimal trade-off between austerity and growth. Our proposals therefore focus on two ideas: first, putting more emphasis on the primary deficit in both the corrective and the preventive arm of the SGP; and second, simplifying and revising the preventive arm, in particular the estimation of potential output. These reforms would make the SGP more effective in reducing debt ratios, reduce the risk of contractionary austerity while allowing for growth, and contribute to economic convergence. A clearer focus of fiscal policy on primary deficits would also sharpen the distinction between fiscal and monetary policy, as monetary policy has no direct influence on the primary balance. Finally, we argue that substantive progress towards European sovereignty would require major reform. Given today's understanding of monetary policy transmission mechanisms, mechanically limiting sovereign credit at an arbitrary debt-to-GDP ratio seems particularly problematic as it can no longer be justified with the aim of avoiding fiscal dominance.
Keywords: 330